The Law of the Marriage Contract for the Visually Impaired in the Perspective of Islamic Law and Madzhab Shafi'i - Fidyani, Diah; Bakri, Mukhlis; Hijazi, Muh Chiar (Journal of Family Law and Islamic Court, 2024)
This research explores the legal aspects of non-verbal marriage contracts (akad nikah tunawicara) from the perspectives of Islamic law and the Shafi'i school of thought. The marriage contract is an agreement between two parties who enter into matrimony through the process of ijab (proposal) and qabul (acceptance). Generally, a marriage contract is deemed valid if it meets the necessary conditions and pillars. However, for individuals with special needs, particularly those who are non-verbal, there are specific methods for conducting the marriage contract. The objectives of this research are: 1. To understand the procedures of a non-verbal marriage contract according to Islamic law. 2. To determine the legal aspects of a non-verbal marriage contract according to the Shafi'i school of thought. This research adopts the library research method, involving the examination of relevant books and literature related to the discussed issues. The findings of this study indicate that: 1. Non-verbal marriage contracts, from an Islamic legal perspective, must adhere to the pillars and conditions of marriage, similar to marriages involving individuals who can communicate verbally. Non-verbal communication can be through understandable gestures, writing, or representation by a proxy. If the individual can write, the marriage contract is valid using that written form, just as it is valid using gestures. This opinion has been agreed upon by scholars. 2. Imam Shafi‘i asserts that a marriage contract in written form is valid, provided there is someone who reads it on behalf of the party involved. If no one reads it on their behalf, the contract is considered invalid. Additionally, Imam Shafi‘i deems a marriage contract valid through gestures for those unable to write, although he suggests combining gestures with written representation if possible.